Potencial de aplicação de marcadores RAPD e de enraizamento de estacas e miniestacas de clones de erva-mate - Silveira, Ronilda Terezinha (2012)
The rescue of selected adult plants and the renewing of explants constitute the greatest challenge to enable the clonal propagation of mate (Ilex paraguariensis St. Hil.). The objectives of this study were to identify and separate clones of the clonal garden by RAPD markers and to evaluate the effect of different doses of indol butyric acid (IBA) on rooting of cuttings and minicuttings of different clones of mate. Three experiments were carried out. The first, young leaves of ten clones had the DNA extracted for testing RAPD markers. The second, new shoots of stump of four clones were used to set up one bud cuttings with one half leaf. The third experiment, rooted cuttings of 20 year-old-trees were used to set up a clonal minigarden to collect minicuttings of one bud and one half leaf. All cuttings and minicuttings were treated with different doses of IBA. The RAPD technique is successful for clone separation and identification, being the primers OPP-03, OPP-06, OPP-15 and OPP-16 the most polymorphic. Single bud cuttings of new sprouts from stumps of some mate clones are capable of rooting, without the need of indole butyric acid. The clones FO10 and FO52 have different capability for rooting. Minicuttings of the clone FO10 root without indol butyric acid.